The role of women in terrorism - Hossain, Ishtiaq (2018)
Contrary to popular belief, women have been participating in acts of terrorism for a very long time. In this paper, answers to the following questions are attempted: 1. Why do women take part in acts of terrorism? 2. What kinds of role do they usually play in terrorist groups? 3. How can this phenomenon be either slowed down or if possible, stopped?